Fully automatic quantification of fibroglandular tissue and background parenchymal enhancement with accurate implementation for axial and sagittal breast MRI protocols. Issue 1 (27th November 2020) - Wei, Dong; Jahani, Nariman; Cohen, Eric; Weinstein, Susan; Hsieh, Meng‐Kang; Pantalone, Lauren; Kontos, Despina
Abstract : Purpose: To propose and evaluate a fully automated technique for quantification of fibroglandular tissue (FGT) and background parenchymal enhancement (BPE) in breast MRI. Methods: We propose a fully automated method, where after preprocessing, FGT is segmented in T1‐weighted, nonfat‐saturated MRI. Incorporating an anatomy‐driven prior probability for FGT and robust texture descriptors against intensity variations, our method effectively addresses major image processing challenges, including wide variations in breast anatomy and FGT appearance among individuals. Our framework then propagates this segmentation to dynamic contrast‐enhanced (DCE)‐MRI to quantify BPE within the segmented FGT regions. Axial and sagittal image data from 40 cancer‐unaffected women were used to evaluate our proposed method vs a manually annotated reference standard. Results: High spatial correspondence was observed between the automatic and manual FGT segmentation (mean Dice similarity coefficient 81.14%). The FGT and BPE quantifications (denoted FGT% and BPE%) indicated high correlation (Pearson's r  = 0.99 for both) between automatic and manual segmentations. Furthermore, the differences between the FGT% and BPE% quantified using automatic and manual segmentations were low (mean differences: −0.66 ± 2.91% for FGT% and −0.17 ± 1.03% for BPE%). When correlated with qualitative clinical BI‐RADS ratings, the correlation coefficient for FGT% was still high (Spearman's ρ  = 0.92), whereas that for BPE was lower ( ρ  = 0.65). Our proposed approach also performed significantly better than a previously validated method for sagittal breast MRI. Conclusions: Our method demonstrated accurate fully automated quantification of FGT and BPE in both sagittal and axial breast MRI. Our results also suggested the complexity of BPE assessment, demonstrating relatively low correlation between segmentation and clinical rating. Abstract :